2004
DOI: 10.1021/ac049788k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hereditary Mutations in the BRCA1 Gene Using Archived Serum Samples and Capillary Electrophoresis

Abstract: Analysis of DNA variation in biological samples most frequently utilizes the polymerase chain reaction (PCR) performed on extracted genomic DNA, followed by visualization of alleles using various methodologies. Few reports have demonstrated that amplification of DNA from plasma and serum samples is possible. We have performed DNA amplification on a large set of serum samples (n = 2955). Here, we report that known hereditary mutations in the BRCA gene can efficiently be analyzed in serum samples collected and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The samples were stored at À25 C for up to 40 years. The samples were genotyped by means of cycling temperature capillary electrophoresis (23), a PCR-based method that has successfully been applied in previous projects investigating Janus serum samples (24,32). Because the DNA is expected to be degraded, we applied a primer design that yielded short amplicons (<100 bases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were stored at À25 C for up to 40 years. The samples were genotyped by means of cycling temperature capillary electrophoresis (23), a PCR-based method that has successfully been applied in previous projects investigating Janus serum samples (24,32). Because the DNA is expected to be degraded, we applied a primer design that yielded short amplicons (<100 bases).…”
Section: Discussionmentioning
confidence: 99%
“…Because the DNA is expected to be degraded, we applied a primer design that yielded short amplicons (<100 bases). This approach has proven to achieve a PCR success rate similar to that seen when using full-length DNA (24). In addition to using a method well suited for the samples at hand, cases and controls were matched for date of sample collection (i.e., storage time).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that known hereditary mutations in the BRCA gene can efficiently be analysed in serum samples (Ekstrm et al, 2004). With a primer design producing less than 100 bp products, we were able to achieve amplification success rates ranging from 83 to 98%, depending on primer pair.…”
Section: Discussionmentioning
confidence: 95%
“…A detailed description of all methodological aspects is published elsewhere (Ekstrm et al, 2004). Briefly, 5 ml of serum were aliquoted to 96-well plates (Axygen, Tamro Medlab AS, Oslo, Norway), followed by microwave boiling at 1200 W for 4 min.…”
Section: Laboratory Methodsmentioning
confidence: 99%